2005
DOI: 10.1681/asn.2004050392
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Attenuates Diabetic Nephropathy in Apolipoprotein E-Knockout Mice

Abstract: In the diabetic kidney, clinical as well as experimental observations have shown an upregulation of growth factors such as PDGF. These studies, however, were not designed to address whether upregulation of PDGF is merely a manifestation of diabetic renal injury or whether PDGF plays an active role in the pathophysiology of diabetic nephropathy. The objectives of this study were first to assess whether PDGF-dependent pathways are involved in the development of diabetic nephropathy and second to determine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 36 publications
5
110
0
Order By: Relevance
“…97 In contrast, in all other injury models tested, blockade of the PDGFR tyrosine kinase was beneficial. Thus, imatinib reduced mesangioproliferative changes in experimental glomerulonephritis 131,132 ; mildly ameliorated both renal functional and structural parameters in diabetic apolipoprotein E knockout mice 133 ; improved survival, renal function, and histology in murine lupus 134 ; and prevented chronic allograft nephropathy after rat kidney transplantation. 135 Finally, another PDGF tyrosine kinase inhibitor, AG 1295, mildly delayed the development of interstitial fibrosis in rats with unilateral ureteral obstruction 136 ; however, at least in the case of imatinib, it is not always clear whether the benefit observed related to inhibition of the PDGFR tyrosine kinase or to inhibition of the c-abl kinase, which also contributes to renal interstitial fibrosis.…”
Section: Intervention Studiesmentioning
confidence: 94%
“…97 In contrast, in all other injury models tested, blockade of the PDGFR tyrosine kinase was beneficial. Thus, imatinib reduced mesangioproliferative changes in experimental glomerulonephritis 131,132 ; mildly ameliorated both renal functional and structural parameters in diabetic apolipoprotein E knockout mice 133 ; improved survival, renal function, and histology in murine lupus 134 ; and prevented chronic allograft nephropathy after rat kidney transplantation. 135 Finally, another PDGF tyrosine kinase inhibitor, AG 1295, mildly delayed the development of interstitial fibrosis in rats with unilateral ureteral obstruction 136 ; however, at least in the case of imatinib, it is not always clear whether the benefit observed related to inhibition of the PDGFR tyrosine kinase or to inhibition of the c-abl kinase, which also contributes to renal interstitial fibrosis.…”
Section: Intervention Studiesmentioning
confidence: 94%
“…decreased macrophage infiltration in the 5/6 nephrectomy nephron reduction model. 50,53,54,[57][58][59] Inflammatory cytokines were decreased by imatinib treatment in the models of anti-GBM and LN and by nilotinib treatment in the 5/6 nephrectomy model. 54,57,59 These findings provide further evidence for the immunomodulatory properties of imatinib and nilotinib.…”
Section: Imatinib In Murine Models Of Kidney Diseasementioning
confidence: 97%
“…49 In addition, a murine model of diabetes (streptozotocin-treated apoE knockout mice) showed attenuated collagen type I and IV production when given imatinib, a finding associated with reduced expression of PDGF, PDGFR and TGF-b1. 50 Thus, imatinib's inhibition of PDGFR signaling is another potential mechanism whereby imatinib reduces fibrosis.…”
Section: Tgf-b Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The therapeutic benefit of imatinib in animal models of kidney diseases was reported and has largely been attributed to its effect on PDGFR. [11][12][13][14][15][16] It is well established that the PDGF-B and -D isoforms induce glomerular mesangial cell proliferation through engagement of the PDGFR-␤. [17][18][19][20] Furthermore, it has been shown that glomerular cell proliferation and extracellular matrix expansion in TSLP-transgenic (TSLP-Tg) mice are closely associated with enhanced expression of PDGF-B and PDGFR-␤.…”
mentioning
confidence: 99%